PENGARUH KUALITAS PRODUK, HARGA, E-WOM TERHADAP KEPUTUSAN PEMBELIAN DAN MINAT BELI ULANG SMARTPHONE XIAOMI PADA MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNRI - ,Tengku Firli Musfar, Muhammad Alqadri , Taufiqurrahman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
This study aims to examine the effect of Product Quality, Price, EWOM on purchasing decisions and repurchase intentions. Primary data was collected with a questionnaire as an instrument and structured interviews were used as a complement in proving the research results. This study used 100 students of the Faculty of Economics & Business, University of Riau as respondents using the Non-Probability Sampling technique. The method used is Explanatory Research with data analysis tests, classic assumption tests, hypothesis testing, and path analysis as the flow of data testing and assisted by the SPSS version 23 application in terms of data processing. The results of this study indicate that the Variables of Product Quality and Price have a significant effect on purchasing decisions and Repurchase Intention, either directly or indirectly. Keywords: Product Quality, Price, EWOM, Repurchase Decisions, Intentions.